Crowdfunding Innovative Ideas: How Incremental and Radical Innovativeness Influence Funding Outcomes. (7th February 2017) - Chan, C. S. Richard; Parhankangas, Annaleena
Abstract : We investigate the effect of innovativeness on crowdfunding outcomes. Because crowdfunding campaigns characterized by greater incremental innovativeness are more comprehensible and generate more user value for typical crowdfunders, incremental innovativeness may result in more favorable funding outcomes. By comparison, campaigns that feature greater radical innovativeness are riskier to develop, harder for crowdfunders to understand and result in less favorable funding outcomes. This negative effect of radical innovativeness may be mitigated by incremental innovativeness, which may help crowdfunders to understand and appreciate radical innovativeness more. A sample of 334 Kickstarter campaigns provides support for our hypotheses.